(untitled) (American Journal of Islam and Society, 2008)
This policy book purports to advise American decision makers about the changes and transformations taking place in Turkey’s politics and foreign policy, as well as their reasons and implications. It further counselsWashington on how to deal with the novelties that they may engender. Graham Fuller argues that Turkey, under Mustafa Kemal Ataturk and his successors, underwent an imposed “cultural lobotomy” designed to induce a national “amnesia” about its Islamic and Ottoman past (p. 17). This condition, however, is ending, for Turkey seems to be experiencing a counter-dynamic and a “return of history,” away from what the author deems a “transient geopolitical aberration from a long norm” (p. 8). Fuller makes his point by asserting, first, that Turkey is again becoming part of the Middle East and examining its historical trajectory and legacies. Second, by highlighting the increasing divergence in Turkish-American relations due to the changing circumstances related to the Soviet collapse and the reordering of European politics, he sees an American regional agenda at odds with Turkish national and geopolitical interests, as well as a Turkish strategic opening to the Muslim world, Eurasia, Russia, and China, as alternative political and economic options. The author’s broad conclusion is that how Turkey will act in the Middle East and the Muslim world will largely depend on the “complex interplay” between the United States, the European Union, and Turkey’s non-western interests (p. 9). Such a “comeback,” in any case, is likely to partially dilute and complicate, as well as enrich and complement, Turkey’s links with the “West” (p. 8) ...